USIKKERHEDSSTRATEGIER: Psykiateres håndtering af terapeutiske krisesituationer med skizofrene patienter - Dupont, Michael (Tidsskriftet Antropologi, 2002)
During the 1990’s, the social sciences have increasingly focused on the structure and function of scientific expert systems, and the nature of expert reflexivity in these particular settings. This article takes a similar focus and presents data from interviews made during an ethnographic fieldwork among psychiatric psychotherapists. The therapists worked with schizophrenic patients in a Danish mental hospital. The article shows some of the major scientific norms structuring the course of daily clinical practice, and highlights how the therapists cope with situations in which they experience uncertainties in the interaction with schizophrenic patients. It is suggested that the therapists deal with these difficulties in terms of specific coping strategies, which seem to neutralise, integrate or symbolise the uncertainties in question. It is then discussed how order and stability are maintained normatively as well as strategically, and how norms and practices are related to one another in this particular environment of experts.